VPH-8 Analysis of 2017 Rabies Suspected Infectious Animal in Riau Province - Anisah Hanoum (Hemera Zoa, 2018)
Known Rabies cases in Indonesia started since Dutch colonialism and firstly reported by Schoorl (1884) in Jakarta on horse. Then cases on buffalo in Bekasi by Doubletree Esser (1889), and on dog found by Penning (1890). While the case in humans known by de Haan (1894) in Cirebon. In mid 1900s, the disease has spread progressively to variety of provinces which historically rabies free regions such as, the West Sumatra, Central Java and East Java (1953), North Sumatra and North Sulawesi (1956), South Sulawesi (1958), South Sumatra (1959), Lampung (1969), Aceh (1970), Jambi and Yogyakarta (1971), Bengkulu, Jakarta and Central Sulawesi (1972), East Borneo (1974), Riau (1975), Central Kalimantan (1978), South Kalimantan (1983), and Flores Island (1997). In early 2000's the spreading extends to Ambon and Seram Islands (2003), Buru Island (2004), Halmahera and Morotai (2005) Ketapang (2005), Bali Island (2008), and then to Bengkalis and Rupat islands in Riau Province (2009). In 2010 it also spreads to Nias and Saumlaki Islands. Java island hrabies-free ad been considered became Rabies-free region in 2004, nevertheless outbreaks reappeared in Garut (2005, 2007), Tasikmalaya (2006) and covering most of West Java starting 2008.Whilest Rabies disease firstly found in Riau province in 1975, but from 1976 until 1981 no case reported, then the case spread out again since 1982 mostly in Riau mainland province except Indragiri Hilir district. All small islands along east side of Sumatra still stated as Rabiesfree region, later the case found on Indragiri Hilir district, and more recent outbreak of rabies also occurred on Rupat and Bengkalis islands starting2009.During 2017 there were 241 biting cases by Rabies suspected infectious animal in Riau Province. Based on distribution of biting cases, the highest occurance is in Pekanbaru 180 cases (75,63%), then Kampar 52 cases (21,85%) and one each are in Kuantan Singingi, Bengkalis, Indragiri Hulu,Rokan Hilir, Rokan Hulu and Siak.